(untitled) (Research, Society and Development, 2021)
Aim: to report the effects of singing music on the interaction with two babies with heart disease who were early hospitalized in the NICU. Method: descriptive, exploratory, qualitative study, carried out from a study of 2 cases. Subjects: 2 newborn babies and their mothers. Both babies with the same cardiac pathology, a girl and a boy, with interventions at 16/23/30 days of life and at 7/14/21 days of life, respectively. Selection criteria: babies admitted to the ICU, whose mothers authorized the proposed intervention and signed an informed consent form. Setting: Neonatal ICU of a reference cardiology hospital in São Paulo. Data collection: Musical interventions composed of three consecutive weekly meetings (between October and November 2019) of a singer, accompanied by an instrumentalist, with the babies and their mothers. The proposal followed a certain structure (dialogue, improvisation, songs and final song) and after each intervention, field (or on board) diaries were prepared describing the effects of singing on babies and mothers, composing a material of 6 diaries. Data analysis: Reading the diaries to carry out descriptive analysis. Results: From the intervention proposal, it was possible to verify the care and attention dedicated to the various sensory, physical and emotional needs of the baby and their parents, enabling support for the bonding process. There were also effects on babies with regard to sleep patterns, sucking, movement, in addition to the influence on heart rate. Conclusion: It was possible to verify the effects of musical interventions in the two analyzed cases.